The Role of Cytokine Gene Polymorphisms in Rehabilitation Outcome After Traumatic Brain Injury - Franca Rosa Guerini; Cristina Agliardi; Milena Zanzottera; Antonio Caronni; Laura Antolini; Chiara Camilla Derchi; Tiziana Atzori; Elisabetta Bolognesi; Jorge Navarro; Mario Clerici; Angela Comanducci (Cells)
Traumatic brain injury (TBI) affects millions of people worldwide and often results in long-term disabilities. Clinical outcomes vary widely even among patients with similar injury severity, partly due to systemic neuroinflammatory responses mediated by pro- and anti-inflammatory cytokines. Genetic polymorphisms in cytokine-coding genes may influence cytokine expression, thereby affecting rehabilitation and prognosis. We analyzed genetic polymorphisms in the TNF-α, IL-6, IL-6 receptor, IL-1β, and IL-10 genes in 28 subacute TBI patients undergoing rehabilitation. Clinical outcomes were assessed using the Glasgow Outcome Scale Extended (GOSE) and domain-specific scales for cognitive, motor, and functional recovery. Results were correlated with genetic profiles to identify potential predictive biomarkers. The IL-6-174 (GG) and IL-6R 1073 (AA) genotypes correlated with worse GOSE scores (p = 0.02 and p = 0.01, respectively). Co-segregation of IL-6-174 - IL-6R 1073 G-A alleles was linked to poorer outcomes (p = 0.01). Patients with the TNF-α-308 (GA) genotype showed less improvement in Barthel and Mobility scores (p = 0.001 and p = 0.01, respectively) and had a higher incidence of post-traumatic confusional state after rehabilitation (p = 0.03). Overall, the TNF-α-308(GA), IL-6 -174(GG), and IL-6R 1073(AA) genotypes negatively impact rehabilitation outcomes, likely due to their role in enhancing neuroinflammation. Larger studies are needed to develop personalized therapies tailored to genetic profiles, aiming to improve rehabilitation outcomes for TBI patients.